2021
DOI: 10.36660/ijcs.20210055
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotective Effect of Nigella Sativa Oil on Heart Tissues of Rats Exposed to Irradition

Abstract: Radiotherapy is an important treatment method for a wide variety of malignancies. Ionizing radiation (IR) is known to generate free radicals in irradiated tissues.¹ Mammalian cells have both enzymatic and non-enzymatic cleansing systems to remove reactive oxygen species (ROS) and reactive nitrogen species (RNS), respectively.² An imbalance favoring the prooxidants and disfavoring the antioxidants, potentially leading to damage, has been called "oxidative stress."³ Efforts to reduce the toxicity of irradiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Mouket et al [ 34 ] demonstrated the radio-protective effect of NSO on salivary glands exposed to total cranial irradiation in terms of a significant reduction in oxidative stress markers and strong antioxidant effects. Additionally, the radio-protective effect of NSO on the irradiated heart was confirmed by Kaplan et al [ 35 ], where NSO significantly decreased TOS and OSI levels in the heart tissue, while TAS levels significantly increased. Moreover, Shahzad et al [ 36 ] found that NSO administration reduced inflammation and collagen deposition in the lungs of ovalbumin exposed rats with a marked reduction in transforming growth factor beta mRNA expression.…”
Section: Discussionmentioning
confidence: 74%
“…Mouket et al [ 34 ] demonstrated the radio-protective effect of NSO on salivary glands exposed to total cranial irradiation in terms of a significant reduction in oxidative stress markers and strong antioxidant effects. Additionally, the radio-protective effect of NSO on the irradiated heart was confirmed by Kaplan et al [ 35 ], where NSO significantly decreased TOS and OSI levels in the heart tissue, while TAS levels significantly increased. Moreover, Shahzad et al [ 36 ] found that NSO administration reduced inflammation and collagen deposition in the lungs of ovalbumin exposed rats with a marked reduction in transforming growth factor beta mRNA expression.…”
Section: Discussionmentioning
confidence: 74%
“…Mouket et al [34] demonstrated the radio-protective effect of NSO on salivary glands exposed to total cranial irradiation in terms of a signi cant reduction in oxidative stress markers and strong antioxidant effects. Additionally, the radio-protective effect of NSO on the irradiated heart was con rmed by Kaplan et al [35] , where NSO signi cantly decreased TOS and OSI levels in the heart tissue, while TAS levels signi cantly increased. Moreover, Shahzad et al [36] found that NSO administration reduced in ammation and collagen deposition in the lungs of ovalbumin exposed rats with a marked reduction in transforming growth factor beta mRNA expression.…”
Section: Discussionmentioning
confidence: 83%